Commissioning and beam characterization of the first gantry‐mounted accelerator pencil beam scanning proton system. Issue 8 (6th July 2020) - Kang, M.; Pang, D.
Abstract : Purpose: To present and discuss beam characteristics and commissioning process of the first gantry‐mounted accelerator single room pencil beam scanning (PBS) proton system. Methods: The Mevion HYPERSCAN employs a design configuration with a synchrocyclotron mounted on the gantry to eliminate the traditional beamline and a nozzle that contains the dosimetry monitoring chambers, the energy modulator (Energy Selector (ES)), and an Adaptive Aperture (AA). To characterize the beam, we measured the integrated depth dose (IDDs) for 12 energies, from highest energy of 227 MeV down to 28 MeV with a range difference ~ 2 cm between the adjacent energies, using a large radius Bragg peak chamber; single‐spot profiles in air at five locations along the beam central axis using radiochromic EBT3 film and cross compared with a scintillation detector; and determined the output using a densely packed spot map. To access the performance of AA, we measured interleaf leakage and the penumbra reduction effect. Monte Carlo simulation using TOPAS was performed to study spot size variation along the beam path, beam divergence, and energy spectrum. Results: This proton system is calibrated to deliver 1 Gy dose at 5 cm depth in water using the highest beam energy by delivering 1 MU/spot to a 10 × 10 cm 2 map with a 2.5 mm spot spacing. The spot size in air varies from 4 mm to 26 mm from 227 MeV to 28 MeV at the isocenter plane with the nozzle retracted 23.6 cm from isocenter. The beam divergence of 28 MeV beam is ~ 52.7 mrad, which is nearly 22 times that of 227 MeV proton beam. The binary design of the ES has resulted in shifts of the effective SSD toward the isocenter as the energy is modulated lower. The peaks of IDD curves have a constant 80%‐80% width of 8.4 mm at all energies. The interleaf leakage of the AA is less than 1.5% at the highest energy; and the AA can reduce the penumbra by 2 mm to 13 mm for the 227 and 28 MeV energies at isocenter plane in air. Conclusions: The unique design of the HYPERSCAN proton system has yielded beam characteristics significantly different from that of other proton systems in terms of the Bragg peak shapes, spot sizes, and the penumbra sharpening effect of the AA. The combination of the ES and AA has made PBS implementation possible without using beam transport line and range shifter devices. Different considerations may be required in treatment planning optimization to account for different design and beam characteristics. Abstract :